Pattern of Organisms and Antibiotics Used in Treating Diabetes Foot Infection - J, Joehaimey; B, Mohamad Adam; A, M Anwar Hau; MK, Kamil; Purany, SP Jaya; I, Saadon; P, Chee Huan; H, Azura (IIUM Medical Journal Malaysia, 2016)
Introduction: The aim of this study is to determine the most common organisms isolated in diabetic foot infection and the most utilised antibiotic regimes as the first line of treatment. Methods: This is a retrospective record review of the National Orthopaedic Registry Malaysia among diabetes mellitus type 2 patients who had foot infections. All identified cases admitted to 18 government hospitals in Malaysia from the 1st January 2008 until the 31st December, 2009 were included in the study. Results: A total of 416 patients were included in the study. The most common organisms cultured were Proteus species (17.5%), Klebsiella species (17.1%) and Staphylococcus aureus (17.9%), while the most commonly used antibiotic was ampicillin/sulbactam (67.5%). None of the patients was appropriately treated with metronidazole, cefoperazone or fucidic acid. All patients were given appropriate antibiotics to treat Serratia infection. Conclusion: Significant number of patients with diabetic foot infections were not treated using appropriate antibiotics as the first line treatment.